The Effect of Website Quality 4.0 and Brand Image Toward Purchase Decision and Customer Loyality at E-Commerce Shopee in Pekanbaru - Jushermi Jushermi; Muhammad Nayoga; Tengku Firli Musfar; Prima Andreas Siregar (West Science Business and Management, 2023)
The study aims to analyze the effect website quality 4.0 and brand image toward purchase decision and consumer loyalty at E-Commerce Shopee. This research is a quantitative research and primary data was collected by questionnaire as an instrument to prove the results of the research. The population in this study is the people of Pekanbaru city who have used E-Commerce Shopee for the last 3 months. The sampling technique used is non-probability sampling with purposive sampling with sample criteria that can be correspondents are people who have transacted using E-Commerce Shopee for the last 3 months, aged 17 years and over and domiciled in Pekanbaru city. The subjects of this study were 120 respondents. For data analyze using path analysis with WARPPLS 7.O. The result shown that website quality 4.0 and brand image have positive and significant effect to purchase decision and customer loyalty in using the E-Commerce Shopee, website quality 4.0 has positive and significantly effect to customer loyalty through purchase decision, brand image has positive and significantly effect to customer loyalty through purchase decision and purchase decision has positive and significantly effect to customer loyalty in using the E-Commerce Shopee in Pekanbaru.